An Exploratory Analysis of Geotagged Photos From Instagram for Residents of and Visitors to Vienna. (February 2021) - Gunter, Ulrich; Önder, Irem
This study uses geotagged photos from Instagram to identify differences between the popular places in Vienna for residents and visitors. Moreover, we explore whether geotagged data can be useful in determining tourism demand in Vienna. The spatial analysis of 627, 632 geotagged photos reveals the top-50 locations in Vienna for all-, local-, and visiting-Instagram users based on three popularity indicators (numbers of likes, comments, and photos). The results show that the top locations unique to local users are closely linked to activities residents usually pursue or location types they usually visit at their place of dwelling. In using geotagged photos to predict actual tourist arrivals to Vienna, we conclude that only the popularity indicators number of likes and number of comments based on the location ID "Vienna, Austria" for visitors to Vienna should be used and not the number of photos, since this indicator does not automatically generate engagement.